Laparoscopic assisted low anterior resection for advanced rectal cancer in a kidney transplant recipient: A case report. Issue 44 (November 2016) - Xia, Zenan; Chen, Weijie; Yao, Ru; Lin, Guole; Qiu, Huizhong
Abstract: Introduction: Development of de novo malignancy has become a major cause of late mortality in solid organ transplant recipients. Surgery is currently the most important treatment of choice for transplant patients with resectable CRC. However, conventional open surgery represents a great risk to these high-risk patients. They seem to benefit more from laparoscopic surgery, based on the favorable oncological outcome and remarkable short-term advantages of this approach. Patient concerns: In this study, we have reported a case of a 50-year-old man who had underwent kidney transplantation for 4 years. He presented with recurrent hematochezia and frequent loose stools for 1 year, and consulted a doctor for recent progressive general malaise and weight loss. Diagnoses: Colonoscopy revealed a near-circumferential mass at the middle rectum about 8 cm from anal verge. Further biopsy confirmed a diagnosis of adenocarcinoma. Following computed tomography demonstrated peripheral lymph node metastasis, but no signs of distant metastasis. Interventions: The patient underwent a laparoscopic assisted low anterior resection with total mesorectal excision for rectal cancer. Concomitantly, a loop transverse colostomy was performed to prevent anastomotic leakage. The surgery was completed within 120 min with a blood loss of 100 mL, and immunosuppressive therapy was not stopped perioperatively. Considering the tumor stage of pT3N1M0, the patient also received adjuvant chemotherapy with a regimen of FOLFOX for 8 cycles. Outcomes: Anastomotic bleeding occurred in this patient about 4 h after surgery, and a control of hemorrhage per anus was performed timely. The following postoperative course was uneventful without any complications, and graft function stayed well. After 4 months of follow-up period, the patient was in a good condition. No evidences of local recurrence and distant metastasis were found. Conclusion: We have presented a case of successful laparoscopic resection for advanced rectal cancer in a kidney transplant recipient. We believe laparoscopic surgery for CRC in transplant recipients is technically feasible and oncologically safe, which could be a preferred option of surgical procedure in the near future.